Konsolidacja spółdzielczego sektora bankowego w Polsce w latach 1998-2004 - Kata, Ryszard (Consolidation of the Cooperative Bank Sector in Poland in 1998-2004, 2006)
The aim of the paper is to show the processes of consolidation of the cooperative bank sector in Poland in 1998-2004 as well as a trial of estimation of their economic effects. In this period the sector of cooperative banks experienced transformation, of which processes of consolidation were the most important element. Their result was the decrease in number of the cooperative banks by about half. However, cooperative sector regained their market position and started to be competitive.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 393-400